Evaluating Factors Affecting Interior Architectural Space Quality to Enhance Spatial Resilience and Human Productivity: An Application of Maslow’s Hierarchy of Needs - Moharam Ghahremani Drvish; Farhang Mozafar; Ceyed bagher Hoseini; Fateme Mahdizadeye seraj (مدیریت بهره وری)
Abstract The aim of the current research is to investigate the relationship between the architectural quality of the interior organizational space and spatial resilience and its impact on employee productivity. This research adopts a qualitative, exploratory approach, is practical in its intended application, and employs qualitative data collection techniques. Data collection procedure in this study involved studying documents, conducting in-depth semi-structured interviews and forming a focus group of experts in related fields. The statistical population of this research included 12 experts from the three fields of architecture, psychology and management. In this study, the qualitative content analysis method was employed for the data analysis, triangulating the findings from the focus group discussions, with previous researches in the field of resilience and spatial quality. The results were then mapped onto Abraham Maslow's Hierarchy of Needs. In the current research, the central role of employee productivity has been considered as an influential variable in connecting all components. The results of the research led to a model whose main axes, that is, biological and psychological factors, satisfaction and sustainability factors, and social, cultural and economic factors, interact with each other in a triangular cycle. By increasing the productivity, it is possible to develop the third axis of social, cultural and economic, the output of which can lead to the development of the quality of the space and the continuity of the flow. Key Words: interior architecture, quality of space, resilience, productivity of human resources.   1.Introduction The aim of the current research is to investigate the relationship between the architectural quality of the interior organizational space and spatial resilience and its impact on employee productivity. This research adopts a qualitative, exploratory approach, is practical in its intended application, and employs qualitative data collection techniques. Data collection procedure in this study involved studying documents, conducting in-depth semi-structured interviews and forming a focus group of experts in related fields. The statistical population of this research included 12 experts from the three fields of architecture, psychology and management. In this study, the qualitative content analysis method was employed for the data analysis, triangulating the findings from the focus group discussions, with previous researches in the field of resilience and spatial quality. The results were then mapped onto Abraham Maslow's Hierarchy of Needs. In the current research, the central role of employee productivity has been considered as an influential variable in connecting all components. The results of the research led to a model whose main axes, that is, biological and psychological factors, satisfaction and sustainability factors, and social, cultural and economic factors, interact with each other in a triangular cycle. 2.Literature Review Human perception of the environment is one of the most central categories in environmental psychology and the process of acquiring information from the human environment. It can be said that human perception is at the center of any environmental behavior because it is the source of all environmental information. Resilience is the ability to bounce back, endure hardship, cope well, hang on to a lifeline, survive well, recover well, show strength, endure hardship (without breaking), be resourceful, and keep moving forward despite setbacks. Determinants of resilience include a set of biological, psychological, social, and cultural factors that interact to determine how an individual responds to stressful experiences (Southwick et al., 2014). Maslow's hierarchy of needs divides human needs into five categories from low to high, namely physiological needs, safety needs, belongingness, esteem and self-actualization. In the course of the "cause and effect" interaction of the main axes of the subject, productivity plays the role of completing a continuous cycle in which the level of non-physical qualities of the space can develop the social, cultural and economic flow through the persuasion of the sense of place (Spitels, 2015). A place is considered a positive emotional connection between a person and a place, and as a result of this cycle, concepts such as the meaning of a place, human interpretations of it, attachments and positive emotions, as well as cultural links between a person and a place are intangible non-physical factors affecting the quality of space. are considered (Haidari & others, 2013). that along this cycle, the productivity of human resources is improved exponentially and continuously. Methodology.3 In the present study, the data and information was collected through document analysis, in-depth semi-structured interviews and formation of a focus group. The sample selection was done using snowball sampling method. Accordingly, semi-structured interviews were conducted with a number of experts in the field of architecture, environmental psychology and management. Data collection continued until the point of data saturation, at which no new theme was identified. To conduct the interview, a clear and uniform protocol was developed and used. In addition, the interviewees represented a diverse range of experts, including architects specializing in general, landscape, energy, and acoustic design, psychologists with cross-cultural, clinical, cognitive, and biological expertise as well as management specialists with backgrounds in public administration and business, technology and human resources to minimize the possible bias of the interviewees. To ensure the validity of the findings, the classification of the basic categories based on which the interview questions were explained was examined by three of the interviewees. In addition, the findings were obtained from the analysis of the semi-structured interviews and focus groups. 4.Results The frequency of propositions reflects the degree of concentration of a particular factor within the group, as assessed by expert opinion. A total of 244 propositions were generated through focused group activities, and the frequency of these propositions within each qualitative component of the space is illustrated in the bar diagram shown in Figure 4. According to the average number of propositions in total, which is 7, the conclusion is that the items that are below the average number are less important and the items or components that are above the average line are of high importance. Therefore, visibility and view, temperature comfort, air quality, light quantity, light quality, acoustic comfort, physical privacy, ease of physical interaction, visual comfort, and ambient noise level, respectively, have the highest effect in providing space resilience, and protection from psychological threats, density of work space, ease of visual interaction, visual privacy, audio privacy and layout have medium and medium to high impact on spatial resilience. A little reflection on the components of the first group, which have the greatest effect on strengthening resilience and long-term and better quality, leads us to the conclusion that satisfying biological and psychological needs have the leading influence on spatial resilience, and that most of these components are included in the scope of functional requirements. 5.Discussion According to the summary of the research results, the research problem centers on three basic axes which include the quality of space, spatial resilience and the productivity of human resources. These three axes are interconnected, forming a repetitive dynamic cycle in which they continuously interact, promote and degrade each other. Therefore, we have achieved a model where the main axes of the research interact with each other in the form of a triangular cycle in which each of them is conceptualized in interaction with the other at the vertices of a triangle. The difference of our proposed model compared to the latest scientific findings is that in previous researches, the continuity of the relationship between productivity and other factors that provide resilience is considered, for example, in the research of Naziachal et al. (2008) which is one of the best examples of research conducted in this field, on the one hand, the role of biological needs as the basic axis of creating physical health has not been addressed, and on the other hand, productivity is only referred to as the output of one-way communication of environmental factors in providing productivity, and naturally, the feedback of productivity in improving the environment has been neglected. On the contrary, in our proposed model, the development of biological and psychological factors that are in accordance with the functional needs is the cause of ensuring the quality of the space, and the response to the mentioned needs through the realization of the quality components of the space, fulfills the resilience in the space. Additionally, in the second core of the model, with the realization of spatial resilience, the development of factors of greater satisfaction and permanence in the space is achieved, and consequently, the possibility of a longer and better quality stay in the space is achieved for the employees and the productivity of the employees has improved. Finally, in the third hub of the model, through increasing productivity, it is possible to develop social, cultural and economic factors. Conclusion.6 Developing the productivity of human resources as the main goal of this research is the result of the previous axis of the model cycle. On the other hand, the quality of the space can improve or degrade the resilience of the environment in the workplace; a resilient environment from this point of view is considered to be an environment that has acceptable architectural space quality. According to the results of matching the subject literature with field research, three main levels of the hierarchy of needs in Maslow's theory have been obtained according to the model diagram. Therefore, the results can be summarized as follows: The classification of Maslow's hierarchy of needs is completely consistent with the triangle (cycle) and confirms it. The beginning of the cycle occurs from a set of biological-psychological factors related to resilience in accordance with the functional needs of Maslow's theory, and their development depends on the degree and quality of the fulfillment of each of the subsequent points, and the continuation of the cycle depends on the speed and quality of the factors that form each side of the triangle. It was found that among the environmental factors contributing to resilience, biological and psychological factors hold the highest priority for initiating the process. If these factors are not provided, the model as a cycle will have no significance. Increasing the level of productivity of human resources has a direct significant relationship with the factors that develop satisfaction and permanence in the space and the quality of presence in the space. Hence, the most important factors, as identified by the experts and supported by the comparison of the findings with other research sources, ranked in the order of the effectiveness are view, temperature comfort, air quality, light quantity, light quality, acoustic comfort, physical privacy, ease of physical interaction, visual comfort, and ambient noise level. The development of productivity will cause the growth of cultural, economic and social factors and will directly lead to an increase in the quality of the space. Therefore, it is of central importance in improving the organization and human resources. Conflict of interest: none